2011
DOI: 10.4097/kjae.2011.61.2.112
|View full text |Cite
|
Sign up to set email alerts
|

The effect of electrically heated humidifier on the body temperature and blood loss in spinal surgery under general anesthesia

Abstract: BackgroundGeneral anesthesia often produces some degree of hypothermia and hypothermia causes much more blood loss during surgery than normothermia. Electrically heated humidifiers (EHHs) have been used for patients under general anesthesia and in the intensive care unit. However, the benefits of the EHH have not been widely reported in the literature.MethodsPatients scheduled for posterior lumbar spine fusion, were randomly assigned to a mechanically ventilated with EHH circuit group or to a conventional resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…Our results showed that use of this unit did not prevent a fall in core temperature, but it was found to attenuate reductions in core temperature from 75 min after anesthesia induction, which is consistent that found by Lee et al [9]. In this previous study, it was found that the use of a HHC did not prevent a temperature fall but that it helped maintain body temperature (35.9 ± 0.4℃ in the study group vs. 35.4 ± 0.5℃ in the control group) during spine surgery [9]. Other warming strategies during shoulder arthroscopy have also been reported [7,8].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that use of this unit did not prevent a fall in core temperature, but it was found to attenuate reductions in core temperature from 75 min after anesthesia induction, which is consistent that found by Lee et al [9]. In this previous study, it was found that the use of a HHC did not prevent a temperature fall but that it helped maintain body temperature (35.9 ± 0.4℃ in the study group vs. 35.4 ± 0.5℃ in the control group) during spine surgery [9]. Other warming strategies during shoulder arthroscopy have also been reported [7,8].…”
Section: Discussionsupporting
confidence: 93%
“…However, blurring of visual field caused by warmed fluid during arthroscopy is of concern. On the other hand, it was recently reported that active warming and humidification of inspired gases helps maintain core body temperature and reduces blood loss during spine surgery [9], but the efficacy of active warming and the humidification of inspired gases during general anesthesia is debatable. We hypothesized that the use of a humidifier and an electrically heated circuit (HHC) would attenuate decreases in core body temperature during shoulder arthroscopy under general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Due to such reasons, we made efforts to keep the temperature of the operating room higher than 30℃ and heat all fluids, including disinfecting fluids, that were injected to the patients; however, temperature drop was not completely inhibited. Thus, it was expected that the breathing circuit with heating function would reduce the temperature drop as described in other studies [4,5]; but there was no effect observed in this study. This would be because of the body exposure during the surgery due to extensive skin loss in the burned patients.…”
Section: Discussionmentioning
confidence: 46%
“…In case where several types of surgery were included, the results might not be accurate since the body exposure would not be constantly controlled. Another study investigated [4] that HBC would decrease the temperature drop in early anesthesia compared to that of conventional circuit by reducing the heat loss due to airway evaporation and conduction in the early stage of hypothermia. The study was carried out in patients who received spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation